Quản trị chuỗi cung ứng (SCM) có ảnh hưởng tích cực tới việc cải thiện lợi thế cạnh tranh, gia tăng hiệu quả hoạt động cho các doanh nghiệp vừa và nhỏ (DNVVN) (Chin & cộng sự, 2012). Trong nghiên cứu này, thang đo vận hành chuỗi cung ứng được kiểm định tr - Lê Thị Minh Hằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
According to Chin et al. (2012), there exists a positive effect of supply chain management (SCM) on improvement of competitive advantage and performance of small and medium enterprises (SMEs). It is the first time a scale used to measure SCM practices has been applied in the context of Vietnam. Specifically, this study measures the SCM practices of 148 SMEs in Danang. The results show that these SMEs focus more on traditional pratices such as paying attention to supplier’s quality, buliding customer relationship, and evaluating customer satisfaction than on other kinds of SCM practices. Also, the paper contributes to the literature by demonstrating the shortcomings of SCM practices of SMEs in Danang and suggesting some policy implications for improvement of SCM practices and enhancement of competitive advantage
Keywords: Supply Chain Management; Small and Medium Enterprises; Supply Chain Management Practices; Measurement